Transport-Geometry Interactions in Li-Ion Cathode Materials Imaged Using X-ray Nanotomography. Issue 7 (4th May 2017) - Nelson, George J.; Ausderau, Logan J.; Shin, SeungYoon; Buckley, Joseph R.; Mistry, Aashutosh; Mukherjee, Partha P.; De Andrade, Vincent
Abstract : Forging a stronger connection between mesoscale geometry, performance, and processing techniques can realize practical approaches for controlling battery performance using mesoscale geometry. To this end, 3D X-ray imaging, microstructural characterization, and computational modeling have been applied to analyze the intercalation behavior of Li(Ni1/3 Mn1/3 Co1/3 )O2 (NMC) cathodes. Samples extracted from pristine cathodes were imaged using X-ray nanotomography. Active material particle geometry was characterized and compared for samples from four cathodes treated with distinct preparation steps. Significant size reduction was observed in calendered and ball milled samples, and distinct differences were observed in particle morphology. Tomographic data for a representative particle was applied in a numerical transport model to assess the effect of particle geometry on intercalation. This assessment proved critical in determining an appropriate estimate of particle size for defining dimensionless parameters that permit rapid estimation of intercalation time. Defining an effective particle radius based on a sphere of equivalent surface area to volume ratio was found to provide the most accurate estimate of intercalation time. Informed by this analysis, dimensionless parameters were used to assess intercalation behavior of the cathode materials. This assessment revealed a substantial change in rate capability connected to particle size reductions achieved in calendering and ball milling.